Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea) - Aquino, Daniel A.; Triapitsyn, Serguei V.; Huber, John T. (Zootaxa, 2016)
Three New World species are transferred from Polynema Haliday to other genera of Mymaridae and redescribed based on examination of their type specimens: Polynema albicoxa Ashmead to Acmopolynema Ogloblin as Acmopolynema albicoxa (Ashmead), comb. n., Polynema porteri (Brèthes) to Agalmopolynema Ogloblin as Agalmopolynema porteri (Brèthes), comb. n., and Polynema giraulti Perkins, for which a lectotype is designated, to Stephanodes Enock as Stephanodes giraulti (Perkins), comb. n. Agalmopolynema shajovskoii Fidalgo, syn. n. is synonymized under Agalmopolynema porteri; Polynema (Dorypolynema) gaucho Triapitsyn & Aquino, syn. n. and P. grenadensis Ashmead, syn. n., are synonymized under Polynema (Dorypolynema) magniceps Ashmead, for which taxonomic notes are given. Caenomymar Yoshimoto, syn. n. is synonymized under Omyomymar Schauff, and its only species Caenomymar howdeni Yoshimoto is transferred to Omyomymar as Omyomymar howdeni (Yoshimoto), comb. n. Gonatocerus chula Triapitsyn & Bernal is transferred to Cosmocomoidea Howard as Cosmocomoidea chula (Triapitsyn & Bernal), comb. n. Erythmelus mirus Girault is transferred to Cleruchoides Lin & Huber as Cleruchoides mirus (Girault), comb. n. and compared with Cleruchoides noackae Lin & Huber, a species introduced from Australia into South America as a biological control agent of Thaumastocoris peregrinus Carpintero & Dellapé (Hemiptera: Thaumastocoridae), an introduced pest of Eucalyptus. Four spelling corrections are made to species names in Cosmocomoidea and Lymaenon Walker.